Exogenous fatty acids protect enterococcus faecalis from daptomycin-induced membrane stress independently of the response regulator liar (2016)
Enterococcus faecalis is a commensal bacterium of the gastrointestinal tract that can cause nosocomial infections in immunocompromised humans. The hallmarks of this organism are its ability to survive in a variety of stressful habitats and, in particular, its ability to withstand membrane damage. One strategy used by E. faecalis to protect itself from membrane-damaging agents, including the antibiotic daptomycin, involves incorporation of exogenous fatty acids from bile or serum into the cell membrane. Additionally, the response regulator LiaR (a member of the LiaFSR [lipid II-interacting antibiotic response regulator and sensor] system associated with cell envelope stress responses) is required for the basal level of resistance E. faecalis has to daptomycin-induced membrane damage. This study aimed to determine if membrane fatty acid changes could provide protection against membrane stressors in a LiaR-deficient strain of E. faecalis. We noted that despite the loss of LiaR, the organism readily incorporated exogenous fatty acids into its membrane, and indeed growth in the presence of exogenous fatty acids increased the survival of LiaR-deficient cells when challenged with a variety of membrane stressors, including daptomycin. Combined, our results suggest that E. faecalis can utilize both LiaR-dependent and -independent mechanisms to protect itself from membrane damage. IMPORTANCE Enterococcus faecalis is responsible for a significant number of nosocomial infections. Worse, many of the antibiotics used to treat E. faecalis infection are no longer effective, as this organism has developed resistance to them. The drug daptomycin has been successfully used to treat some of these resistant strains; however, daptomycin-resistant isolates have been identified in hospitals. Many daptomycin-resistant isolates are found to harbor mutations in the genetic locus liaFSR, which is involved in membrane stress responses. Another mechanism shown to increase tolerance to daptomycin involves the incorporation of exogenous fatty acids from host fluids like serum or bile. This improved tolerance was found to be independent of liaFSR and suggests that there are additional ways to impact sensitivity to daptomycin. Thus, further studies are needed to understand how host fatty acid sources can influence antibiotic susceptibility.